Saunders comprehensive review for the NCLEX-RN examination - Silvestri, Linda Anne. 4 0 16; 5 (St. Louis, Missouri : Saunders, 2008)
A comprehensive guide for the NCLEX-RN examination covering the entire nursing program, with practice questions, detailed rationales for both correct and incorrect answers, test-taking strategies for every question, and accompanying CD.
Includes CD-ROM.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Nursing;National Council Licensure Examination for Registered Nurses;Nursing;National Council Licensure Examination for Registered Nurses -- Examinations, questions, etc.;Study guides.;Examinations, questions, etc.;Study guides; 20; 2